RECIPROCITY AS A CONDITION FOR THE RECOGNITION OF FOREIGN COURT DECISIONS: POLITICAL-LEGAL ASPECT AND MODERN SIGNIFICANCE IN DOMESTIC AND COMPARATIVE LAW - Jakšić, Jelena (Srpska politička misao, 2026)
This paper examines the institute of reciprocity as a condition for the recognition of foreign court decisions, with special reference to Serbian law and comparative legal trends, pointing out its political-legal significance in contemporary relations between states. Reciprocity is analyzed as a traditional mechanism for the protection of state sovereignty and the equality of states, but also as an instrument for regulating international legal cooperation. It starts from the distinction between legal, factual, and presumed reciprocity and their role in ensuring reciprocity in cross-border relations, while indicating a gradual transformation from a formal to a functional approach. The analysis of court practice and comparative law decisions shows an evolution from strict formal to material (factual) reciprocity and an increasingly pronounced tendency for reciprocity to be assumed, instead of being formally proven, whereby the center of gravity increasingly moves towards procedural guarantees, public order, and the principle of mutual trust. Special attention is paid to contemporary solutions in the law of the European Union and other legal systems, as well as the impact of the Hague Convention on the Recognition and Enforcement of Foreign Court Decisions from 2019 [Hague Judgments Convention 2019], which affirms a model based on procedural standards and not on formal reciprocity. Critical analysis shows that formal reciprocity in modern law is gradually losing its role as a general precondition for recognition and is increasingly giving way to functional models, which reflect the need for balancing between the protection of state sovereignty and the strengthening of international cooperation and trust. It is concluded that the domestic legal system already contains elements of this more modern approach, and that further development should be directed towards strengthening convention and supranational mechanisms of recognition, while retaining reciprocity as a subsidiary instrument in the protection of national interests.
Keywords: recognition of foreign judicial decisions; private international law; factual reciprocity; mutual trust; judicial practice